2013
DOI: 10.2169/internalmedicine.52.9277
|View full text |Cite
|
Sign up to set email alerts
|

AA-amyloidosis in Autosomal Dominant Polycystic Kidney Disease Caused by Chronic Cyst Infections Lasting for 30 years

Abstract: We herein report the case of a 66-year-old Japanese woman who was admitted to our hospital due to diarrhea and malaise. She had been diagnosed with autosomal dominant polycystic kidney disease (ADPKD) at 35 years of age and had suffered from recurrent cyst infections since that time. Antibiotic therapy combined with hepatic cyst drainage and cyst sclerosing therapy led to transient improvements each time. At 66 years of age, watery diarrhea occurred. The patient's serum albumin level declined to 1.8 g/dL, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…A previous report showed that a patient with filariasis-a condition associated with chronic inflammation-receiving antifilarial therapy suffered from reversible acquired AA-type renal amyloidosis [15]. In a patient with autosomal dominant polycystic kidney disease, recurrent infections from renal or hepatic cysts lasting 30 years induced AA amyloidosis in gastrointestinal tract [16]. In our case, a localized, yet prolonged infection, around the region of the replaced hip, could have led to secondary amyloidosis.…”
Section: Discussionmentioning
confidence: 51%
“…A previous report showed that a patient with filariasis-a condition associated with chronic inflammation-receiving antifilarial therapy suffered from reversible acquired AA-type renal amyloidosis [15]. In a patient with autosomal dominant polycystic kidney disease, recurrent infections from renal or hepatic cysts lasting 30 years induced AA amyloidosis in gastrointestinal tract [16]. In our case, a localized, yet prolonged infection, around the region of the replaced hip, could have led to secondary amyloidosis.…”
Section: Discussionmentioning
confidence: 51%
“…Chronic infections including tuberculosis, bronchiectasis, osteomyelitis are well‐known causes of AA amyloidosis. Even chronic cyst infections in autosomal dominant polycytic kidney disease reported to be responsible for the development of AA amyloidosis . These cases suggested that, although very unusual, chronic infections including febrile UTIs might cause de novo amyloidosis in a renal transplant patient.…”
Section: Discussionmentioning
confidence: 97%
“…Case reports of association of ADPKD with secondary systemic amyloidosis are on record in the literature (Table 1). [8][9][10][11] The inciting event for such amyloidosis in the reported cases is primarily attributed to chronic renal cyst infection in 2 cases, chronic hepatic cyst infection and pulmonary tuberculosis in one case each. AA amyloidosis is well known to be associated with chronic infections and chronic inflammatory conditions.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…A total of four case reports have documented histological evidence of AA amyloidosis in patients with ADPKD. [8][9][10][11] The etiology of amyloidosis was ascribed to chronic renal cyst infections in two cases, chronic hepatic cyst infections in one case and pulmonary tuberculosis in one case. [8][9][10][11] AA amyloidosis is well known to be associated with chronic infections and chronic inflammatory states.…”
Section: Clinical Discussionmentioning
confidence: 99%
See 1 more Smart Citation